Effectiveness of Self-Affirmation Interventions in Educational Settings: A Meta-Analysis - Berrios-Espinoza, R (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
School and university can be stressful contexts that can become an important source of identity threats when social prejudices or stereotypes come into play. Self-affirmation interventions are key strategies for mitigating the negative consequences of identity threat. This meta-analysis aims to provide an overview of the effectiveness of self-affirmation interventions in educational settings. A peer-reviewed article search was conducted in January 2023. A total of 144 experimental studies that tested the effect of self-affirmation interventions in educational contexts among high school and university students from different social and cultural backgrounds were considered. The average effect of self-affirmation interventions was of low magnitude (dIG+ = 0.41, z = 16.01, p < 0.00), with a 95% confidence interval whose values tended to lie between 0.36 and 0.45 (SE = 0.0253). In addition, moderators such as identity threat, participants’ age, and intervention procedure were found. Through a meta-analysis of the impact of self-affirmation interventions in educational contexts, this study suggests that interventions are effective, resulting in a small mean effect size. Thus, self-affirmation interventions can be considered useful, brief, and inexpensive strategies to improve general well-being and performance in educational settings. © 2023 by the authors.